2008
DOI: 10.1111/j.1472-765x.2001.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal methanogenesis as influenced by individual fatty acids supplemented to complete ruminant diets

Abstract: F. DOHME, A. MACHMÜLLER, A. WASSERFALLEN AND M. KREUZER. 2001. The objective of the present study was to investigate the effects of seven different pure fatty acids on rumen fermentation using the rumen simulation technique (RUSITEC). The fatty acids were supplied to a complete ruminant diet at a proportion of 50 g kg−1 dietary dry matter and compared with an unsupplemented control. Methane release and methanogenic counts were suppressed by the fatty acids C12 : 0, C14 : 0 and C18 : 2 whereas C8 : 0, C10 : 0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 19 publications
5
78
2
2
Order By: Relevance
“…In contrast, Dohme et al (2001) did not observe any effect of capric acid on ruminal methanogenesis. These contrasting observations might be linked to the interaction between capric acid and the basal substrate.…”
Section: Discussioncontrasting
confidence: 64%
See 4 more Smart Citations
“…In contrast, Dohme et al (2001) did not observe any effect of capric acid on ruminal methanogenesis. These contrasting observations might be linked to the interaction between capric acid and the basal substrate.…”
Section: Discussioncontrasting
confidence: 64%
“…Dohme et al (2001) observed the shifts in SCFA proportions pattern towards more butyrate and lower propionate at 30 mg per 50 ml of incubation fluid. The varying effects on proportions of SCFA at different concentrations of capric acid were unexpected.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations